IMPLEMENTASI SISTEM INFORMASI AKUNTANSI BERBASIS KOMPUTER UNTUK PENGOLAHAN DATA KEUANGAN - Prihatin, Titin (www.bsi.ac.id, 2016)
CV .Kurnia Wijaya Nur still have a problem which could deny progress business some record the data of still manual so as to hinder speed in recording and reporting , For finding data took longer, often error occurred in preparing the report , storage evidence transactions are often missing so to prepare reports become longer and inaccurate because to be done manually. From problems that have been analyzed so the creation of a system accounting computer-based with the methods SDLC (Systems Development Life Cycle) used to address problem .Use accounting system based computer can speed up the process record financial transactions and store data is safer financial report be more accurate.Keyword: Accounting System , System Development